Microfluidic fuel cell for off-the-grid applications - Seyed Ali Mousavi Shaegh (2012)
The present doctoral thesis studies air-breathing microfluidic fuel cells with separated fuel and electrolyte streams as well as a membraneless fuel cell with selective electrodes. In order to gain more insight into the physio-chemical reactions, numerical simulation of the in-house developed air-breathing microfluidic fuel cell is formulated and solved using COMSOL Multiphysics. The results from the simulation show that fuel stream at the anode side and its interaction with the electrolyte stream has significant impact on the total fuel cell performance. As the first step for improving the hydrodynamic manipulation of the fuel stream, a flow-through porous anode is introduced. The effects of flow architecture on fuel utilization and the whole cell performance are investigated. Experimental results show that the flow-through porous anode improves the cell current in a long-term performance test as compared to the conventional design with flow-over planar anode. Because of the improved current generation, the rate of carbon dioxide generation in the cell increases. At high current densities, carbon dioxide produced in the channel emerges as bubbles that block and hinders reactant transport to the active sites of the anode.